20.2k views
0 votes
Consider the following function. f(x) = 2x + 5. Place the steps for finding f-1 (x) in the correct order. A. x-2/5= y B. y = 2x + 5 C. y-5 = 2x D. X-5/2=y E. f-1(x) = x-5/2 F.x= 2y+ 5 G. x-5= 2y H. f-1(x) = x-2/5

Consider the following function. f(x) = 2x + 5. Place the steps for finding f-1 (x-example-1
User Iaasgeek
by
5.2k points

2 Answers

6 votes

Answer:

1. y= 2x + 5

2. x = 2y + 5

3. x - 5 = 2y

4. (x-5)/2 =u

5. f^-1(x) = (x-5)/2

Explanation:

:)

User Emelie
by
5.1k points
6 votes

Answer:


\boxed{\sf \ \ f^(-1)(x)=(x-5)/(2) \ \ }

Explanation:

hello,

the easiest way to understand what we have to do is the following in my opinion

we can write


(fof^(-1))(x)=x\\<=>f(f^(-1)(x))=x\\<=>2f^(-1)(x)+5=x\\<=>2f^(-1)(x)+5-5=x-5 \ \ \ subtract \ \ 5\\<=> 2f^(-1)(x)=x-5 \\<=> f^(-1)(x)=(x-5)/(2) \ \ \ divide \ by \ 2\\

so to follow the pattern of your question

y = 2x + 5

we need to find x as a function of y, so let's swap x and y

x = 2y + 5

then subtract 5

x - 5 = 2y

then divide by 2


(x-5)/(2)=y

finally


f^(-1)(x)=(x-5)/(2) \\

hope this helps

User Wxs
by
5.6k points